2001
DOI: 10.2500/105065801781543709
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Computer-Aided Endoscopic Sinus Surgery

Abstract: Functional endoscopic sinus surgery' (FESS) is a common otolaryngologic procedure, with over 250,000 operations performed annually. Computerized surgical navigation systems are available to assist the rhinologic surgeon in the complex dissection required for FESS. Our objective was to determine whether this system provided quantifiable benefits in FESS. We retrospectively reviewed 203 patients with chronic sinusitis who underwent endoscopic sinus surgery, and divided them into two groups based on whether or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 4 publications
(1 reference statement)
1
57
0
1
Order By: Relevance
“…8,9 The most commonly mentioned drawbacks of computer-assisted surgery are increased cost and increased time demands (during both installation and the surgery itself). 4,10,11 In addition, the computer-assisted surgical systems in use today have an accuracy of 0.5 to 2 mm. 8,12 -14 This slight inaccuracy, potentially compounded by errors in image generation and referencing procedures, implies that, although it may serve as an affirming guide, computer-assisted surgery cannot replace a combination of surgical experience and thorough knowledge of the complex paranasal sinus anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The most commonly mentioned drawbacks of computer-assisted surgery are increased cost and increased time demands (during both installation and the surgery itself). 4,10,11 In addition, the computer-assisted surgical systems in use today have an accuracy of 0.5 to 2 mm. 8,12 -14 This slight inaccuracy, potentially compounded by errors in image generation and referencing procedures, implies that, although it may serve as an affirming guide, computer-assisted surgery cannot replace a combination of surgical experience and thorough knowledge of the complex paranasal sinus anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 15 controlled cohort studies identified, 14 were used for meta-analysis. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] One cohort study was excluded from the meta-analysis as it was a cadaveric study that compared the use of IGS, transillumination, sinus probing, and 6-foot Caldwell radiography for mapping frontal sinus margins during osteoplastic flap. 21 One cohort study was a randomized single-blinded clinical trial.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…For total complications, data on 13 studies were collected for meta-analysis. [7][8][9][10][11][12][13][14][15][16][17][18][19] A total of 1119 patients were allocated to the IGS group and 1282 allocated to the non-IGS group. Overall, there were 44 and 81 total complications in the IGS and non-IGS groups, respectively.…”
Section: Perioperative Morbidity For Igs Vs Non-igs Essmentioning
confidence: 99%
“…However, a similarly designed study with 203 subjects had contradicting findings. 11 More recently, 2 separate meta-analyses found no significant difference in subsequent revision rates with or without the initial use of IGS. 4,14…”
Section: Revision Ratementioning
confidence: 98%
“…Four of the 6 studies showed no statistically significant difference in complication rates with IGS, 11,[15][16][17] whereas 2 studies did show a significant difference in major complications with IGS use. One of these studies showed fewer major complications with IGS use (intracranial injury, orbital injury, major hemorrhage, and aborted procedure) but no difference in minor complications (not specifically defined), 10 whereas the other actually showed an increased rate of orbital injuries with the use of IGS but no other significant differences.…”
Section: Utility Of Image Guidance In Endoscopic Sinus Surgerymentioning
confidence: 99%